The rate and associated factors for GFR decline among chronic kidney disease stage 3 patients in HUSM : a retrospective study - Kamarudin, Muhammad Imran (2018)
Introduction: The number of patients diagnosed with Chronic Kidney Disease (CKD) has steadily; other than affecting the health of the individuals, the impact of the disease can also be seen in the national economy as the cost for management and treatment of progressive CKD, in particular end stage renal failure (ESRD) is highly disproportionate to the population of affected patients. Due to the nature of the illness, there is an increased need to detect and manage the CKD at earlier stage of the disease such as CKD stage 3. Hence, identifications of relevant risk factors for Glomerular Filtration Rate (GFR) decline among CKD stage 3 has become the paramount objective of this research endeavour. Methodology: This is a retrospective cohort study involving a review of the medical records and blood investigation result of 142 chronic kidney disease patients in Hospital USM (HUSM) that was diagnosed with CKD stage 3 from 1st January 2008 to 31st December 2016. Other relevant details such as age, gender, aetiology of CKD, HbA1c level, Systolic blood pressure, Serum albumin level, presence of proteinuria and usage of angiotensin-converting enzyme inhibitors (ACEI)/ angiotensin receptor blockers (ARB) were also collected. The association factors with GFR rate changes were analysed using linear and multiple linear regressions. Level of significance was fixed at 0.05. Results: The rate of GFR decline per year among CKD stage 3 is 2.77 mL/min/1.73m2/year. Within 3 year observation, 66.19% of the participants were stable disease (≤ 24.9% GFR reduction) and 33.81% were progressive disease ( ≥ 25% GFR reduction). Predominantly most CKD stage 3 patient remained instage 3 (80.3%) after 3 year, while small numbers progressed to stage 4 (18.3%) and stage 5 (1.4%). There are four factors that were identified from the multiple linear regression analysis that help predicted GFR changes in CKD stage 3; age (0.33 [95% CI: 0.17, 0.49], p value = <0.001), gender (-4.48[95% CI: -7.43,-1.52], p value = 0.003), serum albumin year 3(0.53 [95% CI: 015, 0.90] p value 0.006), usage of ACEI/ARB (- 4.51[95% CI: -8.00, -1.03], p value 0.012). Conclusion: The rate GFR decline per year in CKD stage 3 are comparable with other studies and predominantly the participant remained in CKD stage 3 and more than half have stable disease. Older age is the predominant factor in slower GFR rate decline in CKD stage 3, while normal serum albumin associated with better GFR rate decline compared to low serum albumin. Interestingly, female gender in our study however, was associated with faster GFR rate decline compared to male gender. The usage of ACEI/ARB statistically had shown to have a negative effect on GFR among our participant but there are possible uncountable factors affecting this result, thus need to treat it with caution.